Does It Pour When it Rains? Capital Flows and Economic Growth in Developing Countries - Jean-Louis Combes; Patrick Plane; Tidiane Kinda; Rasmané Ouedraogo (Fondation pour les études et recherches sur le développement international (FERDI), 2017)
This paper assesses the impact of capital inflows and their composition on the real exchange rate and economic growth in developing countries. Capital inflows can directly support economic growth by relaxing constraints on domestic resources, but can also indirectly weaken growth through the appreciation of the real exchange rate. We employ the Generalized Method of Moments (GMM) for dynamic panel data to deal with the endogeneity bias. Using a large sample of 77 low- and middle-income countries over the period 1980-2012, the results clearly show that capital inflows affect directly and indirectly economic growth. Our main findings are as follows: - (i) a 1 percent increase in total net capital inflows appreciates the real exchange rate by 0.5 percent; (ii) the real exchange rate appreciation effect of remittances is twice as big as the effect of aid, and ten times bigger than the effect of FDI; (iii) overall, capital inflows are associated with higher economic growth after netting out the negative impact of real exchange rate appreciation. Doubling capital inflows per capita would increase growth by about 50 percent, resulting in a gain of roughly 2 additional percentage points on top of the 3.7 percent annual growth rate observed within the sample over the period 1980-2012. Keywords : Capital inflows, real exchange rate dynamics, economic growth
Keywords: F3; F4; O4; 330; Capital inflows; real exchange rate dynamics; economic growth